Maternal mental disorders, psychotropic drugs, socioeconomic status, and offspring congenital anomalies - Satu-Maarit Björkstedt; Hannu Koponen; Hannu Kautiainen; Mika Gissler M; P. Pennanen; Johan G Eriksson; Merja K Laine (Journal of International Medical Research)
Objective To evaluate whether there is an association between maternal mental health, purchase of psychotropic drugs, socioeconomic status and major congenital anomalies in offspring. Methods A register-based cohort study of 6189 Finnish primiparous women who had a singleton delivery between 2009 and 2015. Data on pregnancy and delivery outcomes, psychiatric diagnosis, prescription drug purchases and offspring congenital anomalies were obtained from Finnish national registers. Results Severe depressive disorders were diagnosed in 2.0% of women and severe anxiety disorders in 1.1%. During pregnancy, 9.6% of women purchased psychotropic drugs. Of these women, 5.7% delivered an offspring with a major congenital anomaly. Women who purchased psychotropic drugs in pregnancy had an increased risk of delivering a child with major congenital anomalies compared with women who did not purchase psychotropic drugs. Multivariate regression analysis showed that purchase of benzodiazepines increased the risk of major congenital anomalies (odds ratio 2.11 [95% confidence interval 1.17 to 3.81]). Pregnant women purchasing psychotropic drugs more often lived alone and smoked, had higher body mass index, and had lower annual income and educational attainment than women not purchasing psychotropic drugs. Conclusions Benzodiazepine use, but not socioeconomic status, may be associated with major congenital abnormalities in offspring.